Biotransformation of cortexolone to hydrocortisone by molds using a rapid color-development assay - J. Manosroi (2018)
The capacity of 22 molds for 11β-hydroxylation of cortexolone (Reichstein's compound S) to hydrocortisone were assessed. The biotransformation capacity was compared for solid-state and submerged monocultures of molds that were otherwise under identical conditions. Thin-layer chromatography and a novel rapid color-development assay were used to qualitatively establish the ability of fungi to convert cortexolone to hydrocortisone. These assays were validated and supplemented with data from high-performance liquid chromatography to obtain quantitative information on biotransformation. Nearly all the fungi consumed a significant fraction of the cortexolone fed, but only four of them (i.e., two isolates of Cunninghamella blakesleeana, C. echinulata, and Curvularia lunata) yielded measurable quantities of hydrocortisone. Submerged cultures generally gave a significantly greater yield of hydrocortisone compared to equivalent solid-state cultures. © MAIK "Nauka/Interperiodica" (Russia), 2006.